2017
DOI: 10.1007/s11684-017-0529-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and drug resistance characteristics of carbapenem-resistant Enterobacteriaceae in Hangzhou, China

Abstract: With the abuse of antimicrobial agents in developing countries, increasing number of carbapenem-resistant Enterobacteriaceae (CRE) attracted considerable public concern. A retrospective study was conducted based on 242 CRE strains from a tertiary hospital in Hangzhou, China to investigate prevalence and drug resistance characteristics of CRE in southeast China. Bacterial species were identified. Antimicrobial susceptibility was examined by broth microdilution method or epsilometer test. Resistant β-lactamase g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
3
12
1
Order By: Relevance
“…Moreover, the dissemination of bla IMP-4 -producing K . pneumoniae has been increasing[ 23 , 24 ]. NDM-1and IMP-4 were more frequent than KPC-2 and showed a multiclonal background.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the dissemination of bla IMP-4 -producing K . pneumoniae has been increasing[ 23 , 24 ]. NDM-1and IMP-4 were more frequent than KPC-2 and showed a multiclonal background.…”
Section: Discussionmentioning
confidence: 99%
“…Cephalosporinases, which are naturally present in some enterobacterial species, can be mobilized by transposons and migrate via plasmids into other species. Moreover, the abuse of antimicrobial agents increases the number of carbapenem-resistant strains generating a public health concern ( Yang et al, 2017 ). In the Enterobacteriaceae, the bla TEM−1 β-lactamase is the predominant genotype ( Yang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the abuse of antimicrobial agents increases the number of carbapenem-resistant strains generating a public health concern ( Yang et al, 2017 ). In the Enterobacteriaceae, the bla TEM−1 β-lactamase is the predominant genotype ( Yang et al, 2017 ). In our study, we identified both bla TEM−1 and bla ROB−1 β-lactamase genes which are widespread among H. parasuis and Pasteurella spp ( Guo et al, 2012 ; San Millan et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isolates resistant to either or both carbapenems (imipenem and meropenem) tested were classi ed as CRKP [13] . The carbapenemase phenotype was further con rmed by the Carba NP test [14] . MDR, extensively drug-resistant (XDR) and pandrug-resistant (PDR) phenotypes were de ned according to a previous report [15] .…”
Section: Bacterial Strains and Antibiotic Susceptibility Testingmentioning
confidence: 99%